V-C head bus crash probe - New Straits Times, (2011)
KUALA LUMPUR: The independent board of inquiry set up t probe into the Simpang Pulai - Cameron Highlands bus crash will be chaired by Universiti Putra Malaysia vice-chancellor datuk Radin Umar Sohadi.